1995
DOI: 10.3109/01612849509006931
|View full text |Cite
|
Sign up to set email alerts
|

Crisis and the Filial Caregiving Situation of African American Adult Offspring

Abstract: Although there is emerging knowledge about caregiver strain and health, little is known about this linkage from the perspective of African Americans who care for a demented parent. A two-group comparison design was used to examine the caregiving situation and experience of crisis in a preliminary sample of 38 African American adult offspring. Findings showed that subjects spent an average of 4 hours a day on parent care in the previous 6 months, and reported significant caregiver strain. The 17 subjects with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…• caregiver illness possibly leading to death [7,12,13,17,19,26,29,31,38] institutionalization, [7,17,26]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• caregiver illness possibly leading to death [7,12,13,17,19,26,29,31,38] institutionalization, [7,17,26]…”
Section: Resultsmentioning
confidence: 99%
“…Multiple articles espoused the benefits of a nurse in the home aimed at preventing crises by identifying potential problems and helping caregivers to develop new coping strategies [7,12,13,17,28,30,32,39,41]. England et al [12,13,17] provide examples where a nurse can be helpful, such as: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More African American men than Caucasian men experienced physical neglect. This may be attributed to a number of key factors such as caregiver burden and the level of frailty of the victims (England, 1995;Fredman et al, 1995). A substantial number of older Caucasian men, compared to older African American men, experienced physical (46.7%) and emotional (46.7%) abuse (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…Since African American families are the primary source of care for their aging relatives, it is likely the case that these caregivers would also experience significant caregiver burden, especially as they are likely to be caring for individuals with significant disease burden (Fredman et al, 1995). Another study showed that African Americans who provided care to their demented older relatives reported more exhaustion and emotional arousal than those who did not (England, 1995). It has also been shown that African American families are more likely to care for relatives with greater functional and cognitive impairments than Caucasian families.…”
Section: Introductionmentioning
confidence: 97%